The impact of Wisconsin's 1947 and 1949 school legislation on the schools and rural community of Blair, Wisconsin, 1947-1970 - Chenoweth, Leland W. (My University, 1972)
The schools in the community of Blair, Wisconsin, were reorganized following the enactment of the Wisconsin school aid and reorganization law in 1947. The school district did not meet the State Superintendent's recommendations for a good school district. The State Superintendent and the 1947 legislature expected school districts to be created with the capability of offering a quality school program at a reasonable cost. Blair's new school district did not meet these expectations because the pupil enrollment was small and the valuation was low. This paper seeks to discover the factors which influenced the decision to form the district with these inadequacies. Materials were gathered from The LaCrosse Tribune and the Blair Press (1947-1950), minutes of meetings, Biennial Reports of the State Superintendent of Public Instruction, research papers, bulletins, interviews, legislative and court records, magazines, and the observations of Statehouse reporter, John Wyngaard. The local papers were searched quite thoroughly for articles which might have furnished information that would have indicated the public should have been better informed than it was about the purpose of school reorganization. It was discovered that little had been printed about reorganization though much was written about the pending state aid and tax legislation. This work reveals that several factors contributed towards the creation of the unsatisfactory district. Because the purpose of reorganization was not explained to the people, they resisted it in many ways. The public did not participate in overall planning for the reorganization of the counties schools before reorganization orders were issued by the County School Committee. There was no acceptable method to objectively measure whether a school district was satisfactory. The public had no recourse for appeal from reorganization orders. School aid did not furnish an incentive to create a desirable district. Finally there was no agency at the state level to review proposed consolidations of the county school committees to determine whether the district would be capable of offering good programs at a reasonable cost.
Keywords: Educational law and legislation -- Wisconsin.; Schools -- Centralization -- Wisconsin -- Blair; Schools -- Wisconsin -- Blair -- History